The Impact Commercialization of Education in Bagan Asahan Village Tanjung Balai - Zainal Abidin; Kenny Agusto Arie Wibowo; Aswan Aswan; Wulan Sari (Journal of Education and Teaching Learning, 2023)
Education has a significant influence on the nation's life in response to the impacts brought about by the current wave of globalization. Presently, education has become entangled in the currents of capitalization or commercialization, which consequently affect the managerial systems developed and implemented by the educational institutions themselves. This research aims to (i) Identify the forms of educational commercialization, and (ii) Understand the impact of educational commercialization on school dropouts in the Bagan Asahan Village, Tanjungbalai Sub-district, Asahan Regency. This study employs a qualitative, descriptive research design. The selection of informants is done through purposive sampling. Primary and secondary data sources are utilized. Data is collected through observation, interviews, and documentation. The data analysis technique employed is qualitative-descriptive. The results of this research indicate that, 1) The forms of educational commercialization include (a) expensive educational costs, (b) various institutional fees, and (c) trade within the education sector. 2) The positive impacts of educational commercialization for the community are (a) reduced government burden in financing education, (b) increased competitiveness of educational institutions leading to improved facilities and educational quality, (c) increased profits and income for educational institutions. However, the negative impacts are (a) higher education costs, (b) education becoming a business field, (c) emergence of stigmatization and discrimination between the wealthy and the poor, (d) persistent poverty cycles difficult to break through education, (e) privatization of education, and (f) a shift in the mission of education from an academic culture to an economic culture.